Evaluation of the Mechanical Behavior of Local Brick Masonry in Pakistan - Shah, T. M.; Kumar, A.; Shah, S. N. R.; Jhatial, A. A.; Janwery, M. H. (Engineering, Technology & Applied Science Research, 2019)
Masonry is the oldest form of construction in the world [1]. Research shows that it is the most widely used construction material in Pakistan and it has remained as such for more than the past hundred years. The majority of buildings in Pakistan are load-bearing burnt-brick masonry structures. Unfortunately, the brick masonry structures in Pakistan are not designed with respect to any regulatory code, because none exist. Consequently, these structures are not constructed according to a safe design and thus become hazardous and often face considerable damage and sometimes prove to be fatal. This study aims to study the behavior of local brick masonry under normal, shear and thermally challenging conditions and to model its behavior by relating the crushing strength (f’m) to the height-to-thickness ratio and temperature.